Author Correction: SMARCA2-regulated host cell factors are required for MxA restriction of influenza A viruses - Dominik Dornfeld (Nature Portfolio, 2018)
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.